Mammals of the Harrat al-Harrah Protected Area, Saudi Arabia - Seddon, Philip J.; Heezik, Yolanda Van; Nader, Iyad A. (Zenodo, 1997)
(Uploaded by Plazi for the Bat Literature Project) The 12,150 km' Harrat ai-Harrah Protected Area in northern Saudi Arabia was created in 1986 in a landscape of undulating basalt lava fields, gravel plains and sparsely vegetated wadis. Between 1991 and 1996 records of mammals in the reserve have been compiled and surveys and trapping undertaken. A total of 22 species of mammals including three domestic animals have been confirmed within the reserve's boundaries. Harrat ai-Harrah is important for wildlife, including eight species of native carnivores, the Arabian Wolf Canis lupus, the Striped Hyena Hyaena hyaena, and the Caraca1 Felis caracal being among them.